PROSES DAN IMPLEMENTASI PERENCANAAN PENDIDIKAN (Dalam Rangka Pelaksanaan MBSP di Satuan Pendidikan Islam X) - Utomo, Lukito Lebdo (Pascasarjana IAIN Kudus, 2013)
The activation of autonomy and decentralization has an effect to the system of educational institution management. At first,the management system has top down pattern, now it changesinto bottom up pattern. Formulation of the vision, mission,and objectives of educational institution have to formulatedproporsionally by stake holder of educational institution. Planningand implementation process as part of the management of educationhas an important role to achieve the vision, mission, and goals thathave been formulate. Tha paper discusses the process of planningand implementation “MBSP” in Islamic Education Unit X. Withqualitative methods, there in described three pilars in IslamicEducation Unit X, the are “MS”, “PAKEM”, adn “PSM”. Stagesof planning process is done sequence as the preparation procedure“RKS/M”. Implementation of comprehensive planning was donethrough various forums, cordination, syncronization, control, andevaluation.